PERFORMANCE OF POTATOES GROWN FROM TRUE SEED UNDER DIFFERENT ENVIRONMENTAL CONDITIONS IN WEST JAVA - Nikardi Gunadi; Paul M. Harris (Indonesian Journal of Agricultural Science, 2000)
True potato seed (TPS) has been considered as an alternative planting material of seed tuber in potato production, especially in developing countries where good quality of seed tuber at reasonable price is difficult to obtain. This study was conducted to investigate the effects of environment and genotype on potatoes grown from TPS in contrasting seasons and sites in West Java, Indonesia over a period of two years (September 1990-October 1992). Different method of establishing the potato crop from TPS were tested and compared with  ev. Granola established from seed tubers. Data were interpreted in terms of relationships between total and tuber dry matter yield and intercepted radiation (IR). The growth and yield of potatoes grown from TPS were generally better at higher rather than lower altitudes, probably related to the lower temperatures which was reflected in an increase in IR and in the efficiency of conversion of IR into total and tuber dry matter. In the highland, seedling transplants and seedling tubers were both suitable for establishing crops from TPS in the wet season, but not in the dry season. All progenies, in general performed well at the highland especially the medium-late maturing progenies such as HPS 7/13. Atlantic x LT-7 initiated tubers and matured more rapidly than the other progenies and performed well at the lower altitudes. Atzimba x DTO-28 had a more gradual decline in ground cover and was more resistant to late blight than other early-medium maturing progenies. The medium-late maturing progeny. Atzimba x R-128.6 matured later and performed poorly at the lower altitudes.